Kebijakan Pendidikan dan Tantangan Implementasinya di Lembaga Pendidikan Islam - Tengku Darmansah; Putri Suci Ramadhani; Dessy Masliani Br Lubis; Desi Fitriyani Sembiring (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Educational policies in Islamic educational institutions have an important role in realizing educational goals that are in accordance with Islamic values. This research discusses how educational policies are formulated and implemented in the context of Islamic educational institutions, as well as the various challenges faced during this process. Using descriptive qualitative research methods with a case study approach in several Islamic educational institutions, this research identifies main challenges such as limited human resources, lack of in-depth understanding of policies, and difficulties in balancing national policies and Islamic values. The research results show that successful implementation of education policies requires effective management support, competence of teaching staff, and synergy between government, schools and society. By overcoming these challenges, Islamic educational institutions can improve the quality of education and ensure that the policies implemented are in line with the vision of Islamic education.